Do you keep your promise because you want to keep it, or you just want to do what you have promised? - Li, Jingwei (2024)
We keep our promises. However, the reason behind it remains unresolved. We try to explore the two dominant underlying motivations of it (EBE and CBE) using a novel experimental design. In addition, we compare the moral costs of violating different types of promise and separate self-selection effects in people’s promise-keeping behavior.